Integrated transcriptomic and metabolomic profiles reveal the protective mechanism of modified Danggui Buxue decoction on radiation-induced leukopenia in mice - Chen, Wei; Xin, Jiayun; Wei, Xintong; Ding, Qianqian; Shen, Yunheng; Xu, Xike; Wei, Yanping; Lv, Yanhui; Wang, Jie; Li, Zhanhong; Zhang, Weidong; Zu, Xianpeng (Frontiers in Pharmacology, 2023)
Leukopenia caused by radiation hinders the continuous treatment of cancers. Danggui Buxue Decoction (DBD) has been widely used in clinical owing to low toxicity and definite therapeutic effects to increase leukocytes. Meanwhile, icaritin (ICT) has also been proved to have the effect of boosting peripheral blood cells proliferation. However, there is no study to prove the efficacy of MDBD (Modified Danggui Buxue Decoction), a derivative herbal formula composed of DBD and ICT, in the treatment of radiation-induced leukopenia. In this study, we performed a model of 3.5 Gy whole-body radiation to induce leukopenia in mice. The results of pharmacodynamic studies demonstrated that MDBD could significantly increase the white blood cells in peripheral blood by improving the activity of bone marrow nuclear cells, reducing bone marrow damage, modulating spleen index, and regulating hematopoietic factors to alleviate leukopenia. We also analyzed the integrated results of metabolomics and transcriptomics and found that MDBD could relieve leukopenia and alleviate bone marrow damage by targeting steroid biosynthesis and IL-17 signaling pathway, in which the key genes are Jun, Cxcl2 and Egr1. Therefore, our study provides a basis for the effectiveness and compatibility in the combination of traditional Chinese medicine formula and small molecule drugs.